Reduced serum 25(OH)D is closely related to bronchial mucus plug formation in children with mycoplasma pneumonia: A prospective cohort study - Kun, Jiang; Silei, Yan; Sun, Chao; Wenyan, Huang (Frontiers in Public Health, 2023)
Background The relationship between vitamin D nutritional status and the formation of bronchial mucus plugs (BMPs) is unclear. The aims of the current study were to investigate associations between serum 25(OH)D levels, serum inflammatory factors, and clinical characteristics in children with mycoplasma pneumonia (MPP), and to summarize the risk factors for BMPs in children with MPP. Methods Clinical data from 175 children with MPP were collected and analyzed, the children were divided into a BMP group and a non-BMP group. Serum 25(OH)D levels, IL-8, and various inflammatory factors were compared in the two groups. Associations between 25(OH)D levels and IL-8, various inflammatory factors, and clinical characteristics were analyzed, and the diagnostic value of serum 25(OH)D levels was assessed. Results Serum 25(OH)D level was significantly lower in the BMP group (p < 0.05). Serum IL-8 level, percentages of neutrophils, and some inflammatory factors were significantly higher in the BMP group (p < 0.05). Serum 25(OH)D level was negatively correlated with IL-8, neutrophil percentage, various inflammatory factors (all p < 0.05). It was also associated with lobular infection, pleural effusion, mechanical ventilation, and mycoplasma 2,063/2,064 mutation (all p < 0.05). In multivariate regression analysis 25(OH)D [odds ratio (OR) 0.98, 95% confidence interval (CI) 0.97–0.99, p = 0.003], IL-8 (OR 1.02, 95% CI 1.00–1.04, p = 0.002), polylobular infection (OR 1.75, 95% CI 1.17–2.64, p = 0.007), and MP DNA copies (OR 0.98, 95% CI 1.04–1.01, p = 0.022) were independent risk factors for BMPs, and the area under the curve value was 0.915 (95% CI 0.895–0.935). If the serum 25(OH)D level was <50 nmol/L, the respective percentages for sensitivity, specificity, positive predictive value, and negative predictive value were 97, 81, 78.9, and 97.6%. Conclusions Vitamin D deficiency is common in children with MPP, and 25(OH)D levels are closely associated with inflammatory factors and disease severity in children. The serum 25 (OH) D level of MPP children with BMPs was lower than that of children without BMPs. Serum 25(OH)D can be used as a marker for the diagnosis of MPP in children with BMPs.